Garment manufacturing technology - Nayak, Rajkishore; Padhye, Rajiv (Woodhead Publishing is an imprint of Elsevier ; in association with the Textile Institute, 2015)
Garment Manufacturing Technology provides an insiders' look at this multifaceted process, systematically going from design and production to finishing and quality control. As technological improvements are transforming all aspects of garment manufacturing allowing manufacturers to meet the growing demand for greater productivity and flexibility, the text discusses necessary information on product development, production planning, and material selection. Subsequent chapters covers garment design, including computer-aided design (CAD), advances in spreading, cutting and sewing, and new techno.
Keywords: Clothing trade.; Clothing trade -- Technological innovations.; Clothing factories -- Equipment and supplies.; elektronické knihy; electronic books